Topics of Thought The Logic of Knowledge, Belief, Imagination - Berto, Francesco (Oxford University Press, 2022)
This book concerns mental states such as thinking that Obama is tall, imagining that there will be a climate change catastrophe, knowing that one is not a brain in a vat, or believing that Martina Navratilova is the greatest tennis player ever. Such states are usually understood as having intentionality, that is, as being about things or situations to which the mind is directed. The contents of such states are often taken to be propositions. The book presents a new framework for the logic of thought, so understood-an answer to the question: Given that one thinks (believes, knows, etc.) something, what else must one think (ditto) as a matter of logic? This should depend on the propositions which make for the contents of the relevant thoughts. And the book defends the idea that propositions should be individuated hyperintensionally, i.e. not just by the sets of worlds at which they are true (as in standard 'intensional' possible worlds semantics), but also by what they are about: their topic or subject matter. Thus, the logic of thought should be 'topic-sensitive'. After the philosophical foundations have been presented in Chapters 1−2, Chapter 3 develops a theory of Topic-Sensitive Intentional Modals (TSIMs): modal operators representing attitude ascriptions, which embed a topicality or subject matter constraint. Subsequent chapters explore applications ranging from mainstream epistemology (dogmatism, scepticism, fallibilism: Chapter 4), to the nature of suppositional thinking and imagination (Chapter 5), conditional belief and belief revision (Chapter 6), framing effects (Chapter 7), probabilities and indicative conditionals (Chapter 8).